2013
DOI: 10.1590/s0100-29452013000100034
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient signature of Quebec (Canada) cranberry (Vaccinium macrocarpon Ait.)

Abstract: -Fertilizer recommendations for cranberry crops are guided by plant and soil tests. However, critical tissue concentration ranges used for diagnostic purposes are inherently biased by nutrient interactions and physiological age. Compositional data analysis using isometric log ratios (ilr) of nutrients as well as time detrending can avoid numerical biases. The objective was to derive unbiased nutrient signature standards for cranberry in Quebec and compare those standards to literature data. Field trials were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…In case of high phenotypic plasticity of genotypes to nutrient supply, recent research in agronomy showed that plant ionomes can be tightly supervised by balance response models and critical hyper-ellipsoids in the Euclidean space (Hernandes et al, 2012; Parent et al, 2012a; Marchand et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In case of high phenotypic plasticity of genotypes to nutrient supply, recent research in agronomy showed that plant ionomes can be tightly supervised by balance response models and critical hyper-ellipsoids in the Euclidean space (Hernandes et al, 2012; Parent et al, 2012a; Marchand et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the average yield at Site A was 79% higher than the 2014 Québec average conventional production yield [3]. Recent studies in Québec have already reported yield samples as high as 66,000 kg ha −1 [22] although it was established 25 years ago that the potential for cranberry production would be approximately 57,000 kg ha…”
Section: Relationship Between Yield and Wtdmentioning
confidence: 99%
“…The Mahalanobis distance, thanks to the covariance matrix included in its definition, can account for the usual inclined hyper-ellipsoidal shape of plant ionome scatters (Parent et al, 2012; Marchand et al, 2013). …”
Section: Theorymentioning
confidence: 99%